The Effect of Product Quality and Brand Image On Purchase Decisions at PT Bangun Maju Lestari, Jaten District, Karanganyar Regency In 2022 - Rohwiyati Rohwiyati; Yanti Sri Danarwati (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2022)
This study aims to determine the effect of product quality and brand image on purchasing decisions at PT Bangun Maju Lestari, Jaten District, Karanganyar Regency. Either partially or simultaneously. This research is a quantitative case study. Primary data were obtained from direct research by distributing questionnaires. The research population was 50 respondents. The number of samples in this study were 50 respondents. The data analysis technique used is multiple linear regression test, F test, t test, and coefficient of determination test. The results showed that partially product quality (X1) and brand image (X2) variables had a significant effect on purchasing decisions (Y). These three variables have a significant effect on purchasing decisions simultaneously.